Optimalisasi Sarpras Berbasis Teknologi untuk Peningkatan Efektivitas Proses Pembelajaran di Era TQM - Dwi Setyo Astuti; Murwanto Setyo Nugroho (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study examines strategies for optimizing technology-based facilities and infrastructure to enhance the effectiveness of learning through the Total Quality Management (TQM) approach. Technology is viewed as a key component in creating interactive, flexible, and adaptive learning experiences in the digital era. The research employs a qualitative descriptive approach through observations, in-depth interviews, and document analysis at SMP Islam Al Huda Manisrenggo, Klaten Regency. The findings reveal that the implementation of technology-based facilities, such as virtual laboratories and online learning platforms, positively impacts student participation, conceptual understanding, and the efficiency of the learning process. The integration of TQM principles in managing facilities, such as routine evaluations and continuous improvements, has successfully created a learning environment aligned with students' needs and technological advancements. However, the study identifies challenges such as budget constraints, inadequate infrastructure, and limited teacher training. As a solution, it recommends partnerships with external stakeholders, dedicated budget allocations, and ongoing professional development for educators. This research provides valuable insights into effective technology-based facility management and highlights the contribution of TQM to improving educational quality as a strategic step in addressing the challenges of 21st-century education.